FORMATION GEODYNAMICS OF THE INFRASTRUCTURE OF THE CRETACEOUS KONGJU SEDIMENTARY BASIN (SOUTH KOREA) - Utkin V.P.; Khanchuk A.I.; Kasatkin S.A.; Dong-Woo L. (My University, 2007)
It has been established now that strike-slip faulting at the eastern margin of Asia under conditions of lateral compression was accompanied by the formation of their structural parageneses (local extension structures), where sedimentary basins were formed due to subsidences along normal faults. We believe that epicontinental marginal basins of Asia are related to destruction of the crust rather than its subsidence. This concept made it possible to explain periodic processes of volcanism and the delivery of deep mineralized solutions during sedimentation. The infrastructure of most sedimentary basins is characterized, however, by a system of dislocations (folds and fractures) caused by postsedimentary compression of an unknown nature rather than extension, as should be expected. The basins are bordered by strike-slip faults, which isolate the basins from the external influence of regional compression. Consequently, we can assume that the formation of infrastructures of the basins was governed by intrabasin stress fields related to the dynamics of the development of basin-bounding strike-slip faults (hereafter, BB faults) rather than by regional compression.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая